A Faculty Mentorship Program: Supporting, Engaging, and Retaining New Faculty - Susan Lynch; Cynthia Barrere; Lisa G. O'COnnor; Laima Karosas; Jean Lange (Academic Chairpersons Conference Proceedings, 2016)
Schools need to foster growth and retention of new faculty, often content experts with minimal formal academic experience. Compounding factors include inadequate numbers of seasoned faculty due to retirements, burnout, or low salaries. This session will describe a unique evidence-based faculty mentorship program that supports, engages, and retains new faculty.
Keywords: faculty mentor; coach; faculty retention